CORRELATION BETWEEN IFN-ɤ LEVELS, CHEST RADIOGRAPHY AND THE POSITIVITY OF SMEAR SPUTUM IN NEW TB CASES AT THE DR.SOETOMO HOSPITAL - Yessy Puspitasari; Jusak Nugraha (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Tuberculosis is an infectious disease attacking lungs, triggering damage, and pulmonary dysfunction. Host cytokine responses will influence tuberculosis manifestations. The main host immune response is cellular immunity, and Delayed-Type Hypersensitivity (DTH). IFN-γ produced by Th-1, is a major cytokine acting to eliminate TB bacteria through macrophage activation. Chest radiography has an important value for the diagnosis of TB, especially in negative sputum smears. Radiological manifestations depend on several factors including host prior to TB exposure, age, and immune status. Sputum smear is also important in diagnosing, and assessing response to treatment of adult pulmonary TB. A cross-sectional study, comprising a total of 36 new pulmonary TB cases at the Dr.Soetomo Hospital who met the inclusion, and exclusion criteria, were establish. Plasma IFN-γ was examined by ELISA. Chest radiography was divided into three categories based on the National Tuberculosis Association of USA. Sputum smear data were taken from medical records. There were significant correlations between IFN-γ plasma levels with chest radiography (r= 0.365; ρ=0.029), IFN-γ with positive sputum smear (r= 0.447; ρ=0.006), positive sputum smear with chest radiography (r=0.674; ρ=0.001) IFN-γ plasma levels could reflect lesion area on chest radiography, and sputum smear positivity. IFN-γ plasma levels, chest radigraphy, and sputum positivity may reflect a Th-1immune response, so the more severe level of diseases, an immune response Th-1 become more activated.